Occurrence of Fasciola (Digenea: Fasciolidae) Species in Livestock, Wildlife and Humans, and the Geographical Distribution of Their Intermediate Hosts in South Africa—A Scoping Review - Nyagura, Ignore; Malatji, Mokgadi Pulane; Mukaratirwa, Samson (Frontiers in Veterinary Science, 2022)
This review was conducted to provide an update on the status of the occurrence of Fasciola species in livestock, wildlife and humans, and the geographical distribution of snail intermediate host (IH) species in South Africa. The literature search was conducted on four electronic databases using the Boolean operators in combination with predetermined search terms for thematic analysis. Results showed that Fasciola species have been reported in six out of nine provinces of South Africa in the last six decades (1960–2021), with both F. hepatica and F. gigantica infecting vertebrate hosts and F. hepatica and Fasciola spp infecting humans. Results also showed that most studies relied on morphological identification of eggs and flukes without molecular confirmation, which might have led to the misidentification of specimens, especially when immature. Fasciola hepatica has been documented in Limpopo, Mpumalanga, and KwaZulu-Natal provinces. The occurrences of Galba truncatula as the probable snail IH for F. hepatica in the three provinces has been documented while Pseudosuccinea columella has only been documented in Mpumalanga and KwaZulu-Natal provinces. The occurrence of F. gigantica to date has been reported in Mpumalanga and KwaZulu-Natal provinces, with overlapping distribution with F. hepatica. Radix natalensis, the main IH of F. gigantica has been documented in all the three provinces, while the two alien Radix species (R. auricularia and R. rubiginosa) were documented in KwaZulu-Natal province and have been implicated elsewhere with the transmission of F. gigantica. The presence of Fasciola spp eggs and antibodies in humans were documented in the Eastern Cape and the Western Cape provinces, where both P. columella and G. truncatula are known to be present. The prevalence of Fasciola spp infection in livestock ranged from 9.1 to 37.67 %, with an estimated annual financial loss ranging from R44930.26-129901 in cattle production in the Eastern Cape province of South Africa. This review reaffirms the scarcity of information on the occurrence and burden of fasciolosis in South Africa, and further highlights the importance of future research covering all provinces of the country and assessing the public health significance of the disease in resource-poor livestock communities in the areas where the parasite is endemic.